The EU's different modes of defense governance: More European defense, but how? - Niklas Helwig; Tuomas Iso-Markku (EconPol Forum, 2024)
While there is broad agreement on the overall objective of strengthening European defense in terms of both capabilities and industry, the means and ways to get there remain contested. The lack of a unitary vision on European defense is partly due to the division of EU defense efforts into different modes of governance. They reflect the varying rationales and diverging member states' interests that have shaped EU defense cooperation over the years. In the short run, there are tensions between the different modes of EU defense governance. While the "legislative mode" aims for market efficiency, the "coordination mode" prioritizes joint capability development projects. The "financial mode," by contrast, is geared toward the development of defense industry. To overcome existing divisions, the Commission, the Council, and the European Defence Agency must work hand in hand to ensure that current plans for bolstering the European defense industry adhere to the capability needs of the member states' militaries.
Keywords: 330